Revidering av provningsmetod för vattendimsystem - CEN/TS 14972:2008, Annex A.3 - Håkansson,Anders; Langenbach,Daniel (LUTVDG/TVBB-5303-SE, 2009)
This report evaluates an existing method for testing water mist systems - CEN/TS 14972:2008. Annex A.3. The evaluation is to be seen as an analysis of the uncertainties with respect to repeatability and reproducibility of the test. It is concluded that the test method does not meet the standards required to become an EN-standard in its present form. A new concept is presented and verified, bot theoretically and experimentally. This report is to be seen as one step out of many to make the test method acceptable for its purpose.
Keywords: CEN/TS 14972; test method; water mist; watermist; sprinkler; reference test; office test; testmetod; provningsmetod; vattendimma; vattendimsystem; referenstest; kontorstest